Hyperbilirubinaemia: its utility in non‐perforated appendicitis. Issue 7 (17th November 2015) - Sandstrom, Anna; Grieve, David A.
Abstract: Background: The diagnosis of acute appendicitis is made using clinical findings and investigations. Recent studies have suggested that serum bilirubin, a cheap and simple biochemical test, is a positive predictor in the diagnosis of appendiceal perforation and may be more specific than C‐reactive protein (CRP) and white cell count (WCC). The aim of this study was to investigate the utility of the serum bilirubin level in patients with suspected acute but non‐perforative appendicitis. Methods: A retrospective chart review of 213 patients who presented with suspected appendicitis in a 6‐month period to Nambour General Hospital was performed. Serum bilirubin, WCC and CRP were recorded and analysed as to their utility in relation to the final diagnosis. Results: A total of 196 patients underwent an appendicectomy and 41 of these were negative. The specificity of hyperbilirubinaemia for appendicitis overall was 0.83 with a positive predictive value (PPV) of 0.86, compared with CRP (specificity 0.40, PPV 0.75) and WCC (specificity 0.67, PPV 0.85). The area under the receiver operating characteristic curve for bilirubin was 0.6289 compared to 0.6171 for CRP and 0.7219 for WCC. A subgroup analysis of those with complicated appendicitis demonstrated a PPV for bilirubin of 0.66 compared to 0.58 for WCC and 0.34 for CRP in agreement with the literature. Subgroup analysis of hyperbilirubinaemia in simple appendicitis demonstrated a PPV of 0.81 compared to CRP (0.71) and WCC (0.82). Conclusion: Bilirubin had a higher specificity than CRP and WCC overall in patients with appendicitis. Hyperbilirubinaemia had a high PPV in patients with simple appendicitis.